2002
DOI: 10.1016/s0735-1097(01)01817-4
|View full text |Cite
|
Sign up to set email alerts
|

Primary angioplasty and selection bias inpatients presenting late (>12 h) after onset of chest pain and ST elevation myocardial infarction

Abstract: Patients receiving early invasive therapy had lower risk features on presentation. Selection bias may play an important role in choosing these patients' course of treatment and their subsequent outcomes. Certain patients presenting with AMI and duration of chest pain >12 h may benefit from early invasive therapy. These patients could be characterized in a randomized trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 19 publications
0
11
0
1
Order By: Relevance
“…At each phase of the matching process, a greedy approach is employed: an untreated subject is selected for matching to a given treated subject even if this untreated subject would better serve as a match for another treated subject. This method has been used frequently in the medical literature (Aronow et al, 2003;Srinivasan et al, 2003;Vikram et al, 2003;Elad et al, 2002;Sabik et al, 2002), despite its performance never having been rigorously examined.…”
Section: Propensity-score Matching Methodsmentioning
confidence: 99%
“…At each phase of the matching process, a greedy approach is employed: an untreated subject is selected for matching to a given treated subject even if this untreated subject would better serve as a match for another treated subject. This method has been used frequently in the medical literature (Aronow et al, 2003;Srinivasan et al, 2003;Vikram et al, 2003;Elad et al, 2002;Sabik et al, 2002), despite its performance never having been rigorously examined.…”
Section: Propensity-score Matching Methodsmentioning
confidence: 99%
“…Treated and untreated subjects that remain unmatched are then discarded. This method has been used frequently in the medical literature [16][17][18][19][20], despite the fact that its performance has never been rigorously examined.…”
Section: Practical Settings Of Matchingmentioning
confidence: 99%
“…The remaining 21 studies were full-text reviewed, and 4 studies were excluded due to event rates not reported and outcomes of interest not reported. Finally, 18 studies [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] met the inclusion criteria and were included in the meta-analysis.…”
Section: Study Selectionmentioning
confidence: 99%